Contextual Effect of Health Centers and Quality Dimensions of Antenatal Services on Patient Satisfaction in Klaten, Central Java - Rahmawati, Leny; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Puskesmas plays an important role in reducing maternal and neonatal morbidity and mortality. Contextual health centers and dimensions of service quality can improve maternal and child health services. This study aimed to analyze the factors that influence patient satisfactionSubjects and Method: A cross sectional study was conducted in Klaten Regency, Central Java. A sample of 200 pregnant women at the community health centers was selected by simple random sampling. The dependent variable was patient satisfaction. The independent variables were reliability, tangible, empathy, responsiveness, and assurance. The data were analyzed by multiple multilevel linear regression using the Stata 14 application.Results: Patient satisfaction was influenced by reliability (b=0.30; 95% CI= -0.48 to -0.13; p= 0.001), tangible (b= 0.28; 95% CI= 0.14 to 0.42; p<0.001), responsiveness (b= 0.17; 95% CI= 0.07 to 0.27; p= 0.001), and assurance (b= 0.16; 95% CI= 0.04 to 0.28; p= 0.007), while empathy has no effect on patient satisfaction (b= -0.02; 95% CI= -0.28 to 0.23; p= 0.837). Health center had strong contextual effect on patient satisfaction with ICC= 36.4%.Conclusion: Patient satisfaction is influenced by reliability, tangible (physical evidence), responsiveness, and assurance, while empathy has no effect on patient satisfaction.Keywords: satisfaction, puskesmas, multilevel linear regressionKorespondensi: Leny Rahmawati. Program Magister Kesehatan Masyarakat, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: lovejesus251200@gmail.com. Ponsel: +6288981023493.